2020
DOI: 10.21203/rs.3.rs-29398/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of SARS-CoV-2 spike glycoprotein

Abstract: The spike glycoprotein (S) of SARS-CoV-2 mediates attachment of the virus to cell surface receptors and fusion between virus and cell membranes1. The receptor for SARS-CoV-2, like that for SARS-CoV, is the human cell-surface membrane protein ACE22–4. Membrane fusion activity, as for other class-1 fusion glycoproteins, requires S to be proteolytically cleaved into S1 and S2 that remain associated following cleavage4–7. SARS-CoV-2 is thought to have emerged from bats, possibly via a secondary host8,9. To better … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…While the structural integrality of the spikes has a significant effect on the bioassay of the ACE2 binding affinity, the mechanism of this effect is unknown. Several structures with different RBD up states of CoV-2-S are available in the Protein Data Bank (PDB), , but there is no criterion defined to judge whether a conformation is accessible or inaccessible to human ACE2. It is unknown how easily the spike undergoes conformational change from ACE2 inaccessible to accessible.…”
mentioning
confidence: 99%
“…While the structural integrality of the spikes has a significant effect on the bioassay of the ACE2 binding affinity, the mechanism of this effect is unknown. Several structures with different RBD up states of CoV-2-S are available in the Protein Data Bank (PDB), , but there is no criterion defined to judge whether a conformation is accessible or inaccessible to human ACE2. It is unknown how easily the spike undergoes conformational change from ACE2 inaccessible to accessible.…”
mentioning
confidence: 99%
“…55 "Priming" occurs at S1/S2 boundary providing the SARS-CoV-2 S protein with the structural flexibility required for separating S1 and S2. 56 And a subsequent "activation" cleavage at S2´site generates the exposure of FP and its insertion into the membrane. 57 A variety of proteases including, but are not limited to, Furin, TMPSS2, and cathepsin B/L, have been shown to mediate SARS-CoV-2 for priming and activation, [58][59][60] indicating a relatively high degree of flexibility in cleavage mechanisms.…”
Section: Cleavage Motifs and Their Role In Priming And Activating Of ...mentioning
confidence: 99%
“…for RBD-hACE2 binding. 56 A Furin cleavage motif insertion at the S1/ S2 junction of SARS-CoV enhances spike-driven cell to cell fusion. 66 However blockade of the Furin cleavage motif in SARS-CoV-2 affected its entry into the TMPRSS2 + human lung cell line Calu-3.…”
Section: Rbd and Facilitates The Adoption Of An Open Conformation Req...mentioning
confidence: 99%
“…Our previous simulations have shown that binding of LAin the FA site helps to stabilize a locked conformation (9) which appears more condensed than the LA-free closed form) and that the carboxylate head group of the FA makes consistent salt-bridge interactions with the R408, occasional interactions with K417 and persistent H-bonding interactions with Q409, across the locked subunit interfaces (10). Fatty acids have since been retrospectively discovered in the FA sites of spike proteins from SARS viruses that infect other species (11,12). The S1 domain of the spike protein is responsible for attaching the SARS-CoV-2 virus to the host cell by means of interaction with host cell receptors.…”
Section: The Spike Proteinmentioning
confidence: 99%